2019
DOI: 10.1016/j.cmet.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Glutamine-Dependent mTORC1 Activation Ameliorates Liver Cancers Driven by β-Catenin Mutations

Abstract: Highlights d mTORC1 activation is seen basally in pericentral hepatocytes because of Wnt/b-catenin d CTNNB1-mutated liver tumors are positive for GS and p-mTOR-S2448 d CTNNB1-mutated hepatocellular cancers are addicted to mTORC1 for metabolism d Targeting b-catenin-GS-mTORC1 axis in liver tumors may enable precision medicine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 55 publications
4
74
0
Order By: Relevance
“…Glutamine synthase levels also affect mTORC1 activation. In liver cancer with mutations in β-catenin, levels of GS, a target of β-catenin, are increased and its disruption prevents mTOR phosphorylation at Ser2448, suggesting downregulation of mTOR activity [139]. In some cell types, in the absence of glutamine, cells utilize ammonia as an alternative nitrogen source.…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“…Glutamine synthase levels also affect mTORC1 activation. In liver cancer with mutations in β-catenin, levels of GS, a target of β-catenin, are increased and its disruption prevents mTOR phosphorylation at Ser2448, suggesting downregulation of mTOR activity [139]. In some cell types, in the absence of glutamine, cells utilize ammonia as an alternative nitrogen source.…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“…The complexity of the Wnt/β‐catenin pathway combined with the ubiquitous nature of Wnt signaling complicate its blockade. Furthermore, very few agents have been developed that interfere with β‐catenin‐dependent gene transcription, rendering the CTNNB1 mutations clinically, mostly, “undruggable.” A study by Adebayo Michael et al, published in a recent issue of Cell Metabolism , reveals that in β‐catenin‐activated liver cancers the overexpression of the hepatic β‐catenin target gene, glutamine synthetase ( GLUL ) leads to activation of the mammalian target of rapamycin complex 1 (mTORC1) pathway through accumulation of glutamine . These findings open the possibility that mTOR inhibitors could represent a strategy to treat the CTNNB1 ‐mutated HCC that represents almost 30%‐40% of HCC cases.…”
mentioning
confidence: 99%
“…However, the mechanisms by which mTORC1 was activated following an increase in Wnt/β‐catenin activity were not investigated. Adebayo Michael et al showed, with different HCC mouse models bearing a constitutive activation of Wnt/β‐catenin signaling, that all the tumors stained positively for Glul and were also positive for phosphorylated (p‐) mTOR‐S2448, used in the study as a readout of mTOR activation . HCCs not activated for β‐catenin were not stained for p‐mTOR‐S2448.…”
mentioning
confidence: 99%
See 2 more Smart Citations